A Cobb Douglas stochastic frontier model on measuring domestic bank efficiency in Malaysia - Hernandez Montoya, Alejandro Raul; Hasan, Md. Zobaer; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (2012)
Banking system plays an important role in the economic development of any country.Domestic banks, which are the main components of the banking system, have to be efficient; otherwise, they may create obstacle in the process of development in any economy.This study examines the technical efficiency of the Malaysian domestic banks listed in the Kuala Lumpur Stock Exchange (KLSE) market over the period 2005–2010.A parametric approach, Stochastic Frontier Approach (SFA), is used in this analysis.The findings show that Malaysian domestic banks have exhibited an average overall efficiency of 94 percent, implying that sample banks have wasted an average of 6 percent of their inputs.Among the banks, RHBCAP is found to be highly efficient with a score of 0.986 and PBBANK is noted to have the lowest efficiency with a score of 0.918.The results also show that the level of efficiency has increased during the period of study, and that the technical efficiency effect has fluctuated considerably over time.